Alterations of Non Invasive Hemodynamics in Weeks 10 to 14 of Gestation Associated with Preeclampsia and Adverse Perinatal Results (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: maternal hemodynamics; adverse perinatal outcome; preeclampsia; gestational diabetes; perinatal death